Successful social games and their super-power: Big data analytics - Ioana Roxana STIRCU (Database Systems Journal, 2017)
This article is a short presentation of big data analysis and game analysis. The paper describes the case of social games, and observes the huge improvement that big data analysis has on social games and their success. It also contains a presentation of Pokemon GO, and its evolution on the market, from launch until today. A set of metrics and algorithms are proposed, that can be used to improve game features and monetization. In the last section, I apply a Naive Bayes classifier, using WEKA, on a set of data collected from social media networks, to predict how using a game that implies walking influences the amount of daily steps a player makes.